Malva sylvestris leaf powder as a feed additive affects the performance, carcass traits, meat quality attributes, serum antioxidants, stress physiology, intestinal bacterial counts, and gut morphology of broiler chicken - Banday, Mohammad T.; Wani, Manzoor A.; Alqhtani, Haifa A.; Bin-Jumah, May; Rudayni, Hassan A.; Allam, Ahmed A.; Algopishi, Uthman Balgith; Adil, Sheikh (Frontiers in Physiology, 2024)
This study investigated the effect of supplementation of Malva sylvestris leaf powder (MSLP) on the production performance of broiler chicken. Ven Cobb broiler chicks (240 day-old male chicks) were distributed randomly into four treatments, each replicated four times, with 15 birds per replicate. The diets formulated were T1 (control) given basal diet only, T2 (basal diet +1.0% MSLP), T3 (basal diet +1.5% MSLP), and T4 (basal diet +2.0% MSLP). The highest improvement of 3.83% in the average daily gain (ADG) was recorded in the T3 group fed 1.5% Malva powder in the diet compared to the control (P = 0.009). The average daily feed intake (ADFI) tended to decrease with an increase in the dose of MSLP in the diet, with the lowest feed intake in the T4 group fed 2% MSLP. During the overall period (7–42 days), the feed/gain (F/G) ratio reduced significantly (P = 0.048) in the T3 and T4 groups compared to the control. The dressed and breast meat yield was found to be significantly (P < 0.05) higher in the T3 group, with no significant change (P > 0.05) in the thigh yield. The changes in the pH and water-holding capacity (WHC) of breast meat were found to be non-significant (p > 0.05) between the control and various other treatments. Thiobarbituric acid-reactive substances (TBARS) were significantly (P < 0.05) decreased in the T3 and T4 groups. There was no negative effect of including MSLP in the diet on the color coordinates of breast meat among different treatments. Compared to the control, the serum immunoglobulin values increased significantly (P < 0.05) in the T3 and T4 groups. Superoxide dismutase (SOD) showed no difference between various treatments; however, malondialdehyde (MDA) decreased significantly (P < 0.05) according to dietary treatments. Serum cortisol increased significantly (P < 0.05) in the T4 group compared to other treatments. The inclusion of Malva powder in the diet at the 2% level significantly (P < 0.05) decreased the coliform count compared to the control birds. Supplementation with Malva powder resulted in a significant (P < 0.05) increase in the villus height-to-crypt depth (VH:CD) ratio of broiler birds in the T3 and T4 groups. In conclusion, MSLP supplementation at 1.5% and 2% resulted in improved production performance of broiler chicken.